Particularities of hemodynamics and oxygen status in infants and preschool-age children with complicated community-acquired pneumonias - Horodkova, Yu. V.; Kurochkin, Mykhailo; Городкова, Юлія Вячеславівна; Курочкін, Михайло Юрійович (My University, 2020)
Community-acquired pneumonia is an important cause of morbidity in developed countries and an important cause of morbidity and mortality in developing countries [1], especially among children under five years [2], despite advances in prevention and management of pneumonia [3]. The basis for determining the severity of the condition in pneumonias is blood gas analysis [4]. In turn, ultrasonographic measurement of cardiac output is fast and accurate approach for dynamic measurement of heart function and circulatory performance in children with severe pneumonia [5, 6].
Городкова Ю. В. - https://orcid.org/0000-0001-5954-7682; Курочкін М. Ю. - https://orcid.org/0000-0001-7633-5577.
Keywords: pneumonia; child; plasmapheresis; hemodynamics; oxygen consumption